Electrochemistry recent advances - Redlin, Jina (New York, NY, USA NY Research Press, 2015)
This book consists of comprehensive information regarding advanced electrochemistry, outlining the physical phenomena instead of the mathematical formalisms of electrochemistry. It provides detailed information regarding this extensive field analyzing its applications and encompasses various topics like cyclohexane-based liquid-biphasic systems for organic electrochemistry, quantitative segregation of an adsorption effect in the form of defined current probabilistic reactions for catalyzed/inhibited electrode procedures, etc. The aim of this book is to serve as a useful source of reference for chemists, material scientists, physicists, surface scientists, engineers, and especially electrochemists.
Includes bibliographical references.
Keywords: Electrochemistry -- Research